A tensile-compressive asymmetry model for shape memory alloys with a redefined martensite internal variable. (23rd September 2019) - Wang, Longfei; Feng, Peihua; Wu, Ying; Liu, Zishun
Abstract: In this paper, through redefining the martensite internal variable of shape memory alloys (SMAs) based on the Brinson model, we propose the one-dimensional phenomenological constitutive model for SMAs to predict asymmetric behavior during tension and compression. Compared with other models, the presented model is much more continuous and efficient by using a novel expression to describe the variation in the martensitic fraction. The numerical results show that our model can successfully predict the asymmetric behaviors of SMAs during multiple tensile-compressive cycles under arbitrary temperatures. Moreover, the proposed model expands its applicable scopes by revealing the internal sub-loops of SMAs, which are caused by incomplete martensitic transitions during tensile-compressive processes. The results of numerical examples show reasonable agreement with the experimental data, which confirm the reliability of the proposed model in applications.